(untitled) (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2021)
The power of images, and more generally of representations, lies not so much in their ability to document reality, but in the power to shape and mould it, a priori and retrospectively. The development and diffusion of technological tools which help to produce representations and their dematerialization, which has exponentially increased the speed and breadth of their dissemination, are factors only in the power of democracy. Excluding the well–known problems related to the ‘digital divide’, there is actually a serious problem of geographical literacy, that is, the lack of knowledge and skills necessary to be able to critically and consciously approach the production, reading and understanding of representations.